Effectiveness of revenue assurance and fraud management process in Banglalink Digital Communications Ltd - Shila, Mithila Ali (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.